Tech-tied or tongue-tied? Technological versus social trouble in relational video calling - Rintel, Sean (HICSS'46, 2013)
Maintaining a relationship via video calling requires intertwining relational and technological talk. Using detailed qualitative analysis of transcripts from naturalistic recordings of couples in a video calling field trial, this paper explores how couple members use the possibility of technological distortion as a resource for negotiating around the problem of inattentive or inappropriate responses. Inattention may be cast as technological trouble, and, conversely, the technology can be blamed for an apparently relationally inappropriate response. It is argued that research on technologically mediated relationship creation and maintenance should not treat technology as simply a container of relationships or a variably rich transmission system for relational material. Rather, mediation should be explored as a fundamental participant concern in online relationship research.